Cohesive approach for high-resolution seismic using inversion & Imaging in Malaysian carbonate field - Bashir, Y. (International Petroleum Technology Conference (IPTC), 2019)
A majority of remaining proven Oil & Gas reserves is contained by Carbonate reservoir, and much more complicated to explore as imaging of the Carbonate rocks is poor. In case of Carbonate data, seismic diffraction imaging has contributed to an enhancement in the quality of seismic but there is still lack of understanding the lithology and impedance contrast which can be defined by the seismic inversion. In contrast, to the conventional process, an integration of seismic inversion methods are necessary to understand the lithology and include the full band of frequency in our initial model to incorporate and detail study about the basin for prospect evaluation. In this paper, an integrated approch is developed for better deleniation of subsurface structure and lithologies. Seismic post stack inversion technique is applied to the Carbonate field to study Electroficies and lithofacies of subsurface strata for better and detail study of the reservoir. Â© 2019, International Petroleum Technology Conference